(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The healing of wounds is a complicated biological process impaired by several factors, and conventional treatments often result in undesirable side effects. Natural compounds have emerged as favorable alternatives due to their reduced side effects. C-phycocyanin (C-Pc), a natural phycobiliprotein derived from Spirulina platensis, shows promise in wound healing but is hindered by poor stability and low bioavailability. This study aimed to develop a hydrogel-based delivery system for C-Pc to enhance its stability and therapeutic efficacy in wound healing. We synthesized a grafted gum hydrogel to encapsulate C-Pc, ensuring its sustained release. The hydrogel’s physical properties, including clarity, pH, spreadability, and rheological behavior were characterized. The encapsulation efficiency, in-vitro release profile, antioxidant activity and adhesion were assessed. Furthermore, the hydrogel’s impact on wound healing was evaluated through in-vivo studies and assessments of skin irritation potential. The optimized hydrogel demonstrated excellent physical stability, appropriate viscosity and significant bioadhesive properties, making it suitable for topical application. The encapsulated C-Pc exhibited a controlled release, enhanced antioxidant activity, and greater wound-healing efficacy than free C-Pc. In-vivo studies confirmed accelerated wound closure with no irritation or allergy, suggesting high biocompatibility and therapeutic potential. Developing a C-Pc encapsulated hydrogel presents a promising approach to improving wound care. This innovative approach not only stabilizes C-Pc but also enhances its healing properties, providing a safe and effective option for patients. This study paves the way for a novel formulation with translatory potential.